Ressocialização: depoimentos de professores e mães de adolescentes da Fundação CASA - Ketelhut, Marcos Rogério Chiesa (2012)
There are many factors that lead a teenager to commit an act of transgression in society today. Considering that are regarded as forming, as it is not yet adult but not a child anymore. Many speeches have concerned their training and education. In spite of various discourses (medical, psychological, historical, social and cultural rights, among others) many still commit acts considered violent and end up, deprived of liberty, being compulsorily enrolled in a school with socialization, and educational measures, after a sentence by court of law. It is therefore important to research the conceptions of this process, since the regular formal school education is considered an important step in the life of every individual. This study is based in authorities who have studied the situation of young offenders and the processes of socialization within institutions. Such as Goffman (2007) which addresses the issue of stigma, Dubar (2005) and Berger and Luckmann (1985) on the (re) construction of personal and professional identities, Becker (2008) and Velho (1981) on the issue of deviation. This study aimed to analyze the concept of teachers who have taught students who have been admitted to the CASA Foundation and the conception of mothers of these teenagers who were interned in the Fundação CASA, in São Paulo, about the process of rehabilitation of these adolescents. Based on the testimony of three former Fundação CASA professors and three mothers of adolescents who were interned in Fundação CASA, the data were analyzed in order to answer the question that guided this research: to determine whether the school and the internation contributed to the rehabilitation of these adolescents. The analysis and reflection on these data showed that on the one hand, teachers varied in the statement that their own classes and Fundação CASA have contributed somehow to the process of resocialization of their students. On the other hand, mothers were unanimous in their assertion that they believe in the real possibility of rehabilitation of their adolescents who were admitted to an Fundação CASA.